Role of FoxO1 in acne and effect of isotretinoin on FoxO1 expression - Parul Kamboj; Geeti Khullar; Sanjeev Handa; Arnab Pal; Uma Nahar Saikia; Dipankar De (Wolters Kluwer Medknow Publications, 2024)
Background: Nodulocystic acne is a severe type of acne that is known to improve after treatment with isotretinoin. Melnik has hypothesized a unifying concept on the mechanism of acne pathogenesis involving altered expression of Forkhead box O transcription factor (FoxO1) and role of isotretinoin in improving acne via modulating this pathway. Aim: To evaluate the pathway proposed by Melnik in acne pathogenesis by analysing the difference in the expression of FoxO1, peroxisome proliferator-activated receptor (PPARγ), and androgen receptor (AR) between acne patients and non-acne controls and the effect of treatment with isotretinoin on change in expression of these genes in acne patients. Results: The gene expression of FoxO1 was non significantly higher in acne patients as compared to controls. After treatment with isotretinoin, a significant decrease in FoxO1 expression in acne patients at mRNA (P = 0.05) level was observed. There was a significant decrease in grade 3 positivity of FoxO1 at protein level (P = 0.0009). A decrease in androgen receptor positivity (P = 0.055) at protein level was also observed. Conclusion: Reduction in FoxO1 expression appears to be an important mechanism of action of isotretinoin in acne.